Reversible Cerebellar Ataxia: A Rare Manifestation of Metronidazole Toxicity - Ranjan, Abhay; Sinha, Neetu (Nepal Journal of Neuroscience, 2024)
Metronidazole is a 5-nitroimidazole antibiotic, which is commonly used and cost-effective treatment for parasitic and anaerobic infections. It is generally safe and well tolerated but have minor side effects like nausea, metallic taste and abdominal cramps. Neurological adverse effects are rare but may include headache, confusion, vertigo and peripheral neuropathy etc. Metronidazole‑induced encephalopathy (MIE) is a serious adverse effect which includes cerebellar ataxia, seizure and altered sensorium . A 28 years male patient presented to us with unsteadiness of gait and dysarthria of ten days duration. He was diagnosed with amoebic liver abscess two months back and was on oral metronidazole 400 mg thrice daily. Cerebellar examination revealed horizontal nystagmus on lateral gaze and a wide based gait. MRI brain showed bilateral symmetric T2/FLAIR hyperintense lesions involving dentate nucleus of cerebellum, dorsal pons and splenium of corpus callosum with diffusion restriction of splenium of corpus callosum [Figure-1]. Two weeks after stoppage of drug patient showed improvement in neurological and radiological features. The characteristic MRI feature of MIE is the T2W and FLAIR symmetric hyperintensity of the cerebellar dentate nuclei mimicking a headphone, also known as headphone sign [2]. Other usual locations of lesion are brainstem and splenium of corpus callosum which are always bilateral and symmetric [3]. The differentials for dentate nuclei involvement are Wernicke’s encephalopathy, drugs (isoniazid and cycloserine), infectious and neurodegenerative disease [4]. This case highlights the importance of knowing the classical MRI brain pattern of metronidazole induced neurotoxicity, as stopping the drug leads to reversal of radiological lesion and neurological symptoms.